Characteristic of Steady-State Flow Force on the Cone Valve Based on Orthogonal Test Method - Liu, Xiumei; He, Jie; Ma, Jichao; Li, Beibei; Xiang, Shaobin; Zhang, Yujia; Liu, Qihang; Xie, Fangwei (Frontiers in Energy Research, 2022)
The valve core will be suffered from the negative impact derived from flow force, so flow force is the fundamental reason that affects the control performance of a hydraulic valve. A mathematical model of the axial steady-state flow force on the cone valve core is proposed, in order to master the principle and characteristics of steady-state flow force. For understanding the dynamic changes of the steady-state flow force, a two-dimensional axisymmetric model is built to discuss the value of flow force. Then geometric parameters and operating conditions influencing factors are discussed by the orthogonal test-optimization method. The main significant factors affecting the performance of steady-state flow force on the internal flow cone valve core are determined by extreme difference analysis, which are the opening and pressure differential, respectively. Furthermore, a test ring is built to measure the flow force. The results show that the greater the differential pressure is, the greater the flow force is. And the flow force does not increase linearly, but increases first and then decreases with the increase of the opening. The studies extend the knowledge of compressible flow force prediction, and guide the design optimization of the valve.